2012
DOI: 10.1073/pnas.1106877109
|View full text |Cite
|
Sign up to set email alerts
|

Extensive X-linked adaptive evolution in central chimpanzees

Abstract: Surveying genome-wide coding variation within and among species gives unprecedented power to study the genetics of adaptation, in particular the proportion of amino acid substitutions fixed by positive selection. Additionally, contrasting the autosomes and the X chromosome holds information on the dominance of beneficial (adaptive) and deleterious mutations. Here we capture and sequence the complete exomes of 12 chimpanzees and present the largest set of protein-coding polymorphism to date. We report extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
80
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 38 publications
7
80
2
Order By: Relevance
“…In comparisons limited to a small number of genes, Satta (2001) found higher p N /p S in humans than in chimps; this difference has been confirmed in genome-scale analyses (Hvilsom et al 2012). p N /p S is also higher in humans (0.35) than in mice (0.19; Halligan et al 2010) and rabbits (0.05; Carneiro et al 2012), which is consistent with substantial differences in f9 n .…”
Section: Population Size and Protein Polymorphismsupporting
confidence: 71%
“…In comparisons limited to a small number of genes, Satta (2001) found higher p N /p S in humans than in chimps; this difference has been confirmed in genome-scale analyses (Hvilsom et al 2012). p N /p S is also higher in humans (0.35) than in mice (0.19; Halligan et al 2010) and rabbits (0.05; Carneiro et al 2012), which is consistent with substantial differences in f9 n .…”
Section: Population Size and Protein Polymorphismsupporting
confidence: 71%
“…Using McDonald-Kreitman-type analyses, we have previously reported that, in the Central chimpanzee lineage, 30-40% of amino acid changes on the X chromosomes are estimated to have been fixed by positive selection, whereas the autosomes do not show significant signs of positive selection (9). A similar conclusion was recently reached for the human X chromosome (10).…”
supporting
confidence: 58%
“…In nonhuman primates, however, some studies have reported much lower ratios. For example, a recent genome-wide resequencing study in central chimpanzees (Pan troglodytes) found a ratio of near 0.5 (Hvilsom et al 2012). A similar ratio was observed in Chinese and Indian rhesus macaques (Macaca mulatta), using shotgun sequencing data (Gibbs et al 2007).…”
mentioning
confidence: 81%